Chiral, pH responsive hydrogels constructed by N‐Acryloyl‐alanine and PEGDA/α‐CD inclusion complex: preparation and chiral release ability. (27th July 2015) - Liu, Jie; Cheng, Ru; Deng, Jianping; Wu, Youping
Abstract : Chiral, pH‐responsive hydrogels are constructed by poly(ethylene glycol) diacrylate/ α ‐cyclodextrin (PEGDA/ α ‐CD) inclusion complex and L‐ N ‐acryloyl‐alanine or D‐ N ‐acryloyl‐alanine (L‐NAA or D‐NAA) by an effective free radical polymerization approach. PEGDA containing two C=C end groups was used simultaneously to introduce α ‐CD units in the resulting hydrogels and to serve as a cross‐linking agent, by which forming the designed hydrogels in quantitative yield. Hydrophilic α ‐CD moieties acted as pore‐forming agent, while the L(D)‐NAA‐based polymer chains bearing –COOH groups enabled the hydrogels to display remarkable swelling–deswelling behavior in response to pH variation. The chiral NAA monomer‐derived polymer chains rendered the hydrogels with intriguing optical activity, according to circular dichroism spectra. Scanning electron microscopy revealed the uniformly porous microstructures of hydrogels. More remarkably, the L‐NAA‐based hydrogels preferentially adsorbed trans ‐4‐hydroxy‐d ‐proline and preferentially released trans ‐4‐hydroxy‐l ‐proline, while D‐NAA‐based hydrogels provided opposite results. The hydrogels also demonstrated remarkable enantioselective release ability towards chiral drug ibuprofen. Copyright © 2015 John Wiley & Sons, Ltd.